Teacher Professional Development in Education 4.0: The Role of ePortfolios and Open Badges - Korhonen, Anne-Maria; Donaldson, Lisa; Kunnari, Irma (Journal of Technical Education Science, 2022)
ePortfolios and Open Badges support learners in taking responsibility for the learning process. When they choose ePortfolio tools by themselves, it supports a continuous learning perspective. Open Badges are used for the accreditation of competences that are demonstrated in ePortfolios. The concept of Open Badges is also used as a guiding and scaffolding tool in learning processes. Consequently, this is a case study in which ePortfolios and open badges were implemented in a professional learning and competence demonstration process with Vietnamese teachers in the EMVITET project. The project took three years, during which teachers learned to implement innovations in their pedagogy, technology and learning ecosystems in their teaching practices. Finally, the ePortfolios were assessed, and accreditations were given. The results of this case study show that teachers demonstrated their competences well in their ePortfolios. However, there are some areas of development in guiding and combining ePortfolios and Open Badges while supporting teachers’ careers and continuous learning.